A Study of Palladium (II) Schiff Base Ligand Complexes of Benzofuran and Its Schiff's Bases: Characterization and Decomposition Studies of Palladium(II) Schiff Base Ligand Complexes of Benzofuran (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The palladium(II), copper(II), cobalt(III) and ruthenium (III) Schiff base complexes with 2-(5,6-Dihydro-benzo[4,5]imidazo[1,2-c]quinazolin-6-yl)- 6-methoxy-phenol (L1), 4-(5,6-Dihydro-benzo[4, 5]imidazo[1,2-c]quinazolin-6-yl)- 2,6-dimethoxy-phenol (L2), 4-Chloro-2-(5,6-dihydro-benzo[4,5]imidazo[1,2-c] quinazolin-6-yl)-phenol (L3) , 4-Bromo-2-(5,6-dihydro-benzo[4,5]imidazo[1,2-c] quinazolin-6-yl)-6-methoxy-phenol (L4), were summarised as dichloromethyl, ethanolbenzene medium, all of which are strong stable, long-term in air, characterised by different physicochemical technologies. The complexes are water insoluble but DMF and DMSO soluble. Yet ethanol and methanol are readily soluble in ruthenium and palladium complexes. The experimental evidence on the complex elemental analysis is well in line with that of the formulation being proposed. The observed molar conductance values are consistent with the non-electrolytic properties of the preparations except for the Co(III) complexes, which are electrolytes, for all the complexes of 10−3 M DMF solution. By analysing different physicochemical techniques, the structures of the prepared complexes are proposed. Palladium (II) complexes are based on experimental results, showing slightly distorted flat geometry with a 11 (Mligand) ratio of all ligands. The complexes [12 (Mligand) and 111 (Mligandphen)] are copper(II), and cobalt(III)], while octaheral geometry is present. The octahedral geometry exhibits for the ruthenium complexes in a 111 (M ligand phen) ratio. The proposed stoichiometry for prepared complexes is verified by thermographometrical studies. In addition, thermographs demonstrate the existence in the complexes studied of the latticecoordinate water molecules. The experimental weight losses, which lead to the successive degradation of metal complexes, are very much in line with the values measured. The last step is the formation of oxides such as PdO, CuO, CoO and Ru2O3. The decomposition is completed. The single crystal structure of 3a was analysed in detail, a palladium-Schiff base complex. However the single production of crystal was not successful for the remaining complexes.